Health and social consequences of the use of psychoactive substances - Kozłowska, Ewelina; Marzec, Agnieszka (Journal of Education, Health and Sport, 2017)
Today is observed the phenomenon of uncontrolled use of drugs including younger and younger age groups. In adolescence and adulthood there is a significant intensification of this phenomenon. This is particularly worrying because of the serious consequences of drug use and abuse of psychoactive substances. In their consequences leading to development of a number of somatic diseases, it contributes to the pathology of many social life. The aim of the study is to present health and social consequences resulting from the use of psychoactive substances. The paper discusses in detail the effects of consuming alcoholic drinks, smoking, drug use.